Kenyamanan Termal Ruang pada Rumah Tradisional Studi Kasus Bale Paon dan Bale Dangin Desa Penglipuran - Anak Agung Ngurah Aritama; Gede Windu Laskara; Ida Ayu Shanty Pradnya Paramitha; Ardina Susanti (Universitas Sebelas Maret Surakarta, 2025)
The level of thermal comfort is influenced by climate factors and human factors and perceptions of space, changes to space will affect the level of comfort of the space. This study aims to determine the level of thermal comfort of the space in Bale Paon and Bale Dangin in traditional houses in Penglipuran Village. This article discusses the influence of space design on the level of thermal comfort in traditional houses in Penglipuran Village, Bangli, especially in the Bale Paon and Bale Dangin buildings. This study uses a quantitative method with data analysis using Building Performance Simulation using software. The results are in the form of thermal performance modeling and parameters that affect the comfort of space in traditional houses in Penglipuran Village. Factors that affect the thermal conditions of space include the layout and orientation of the building mass, the shelter and building envelope around the building mass, and building materials that form the walls, floors and roofs.